Investment and production : a study in the theory of the capital-using enterprise - Smith, Vernon L. (Cambridge : Harvard University Press, 1961)
Developing a unified theory of production and investment, Vernon L. Smith explores the empirical and theoretical nature of the interdependence between (3z(Bshort-run(3y (Bcurrent account production decisions and (3z(Blong-run(3y (Binvestment planning, taking into account such technological factors as equipment replacement. The book builds an explicit theory of production planning by integrating production, investment, and equipment replacement policy, derives the decision implications of the use of durable capital goods, and examines the production function concept and the production decision process in engineering design and in general business practice.s
Includes bibliographical references and index
mf 25/01/2019
Loan
Keywords: Capital investments; Replacement of industrial equipment